Transcriptional regulation of the Drosophila-raf proto-oncogene by the DNA replication-related element (DRE)/DRE-binding factor (DREF) system. - Ryu, J R (1997)
The DRE/DREF system plays an important role in transcription of DNA replication genes such as those encoding the 180 and 73 kDa subunits of DNA polymerase alpha as well as that for encoding PCNA. In this study, we found two sequences homologous to DRE (5'-TATCGATA-3') in the 5'-flanking region (-370 to -357 with respect to the transcription initiation site) of the D-raf gene and confirmed transcriptional activity through gel mobility shift assays, transient CAT assays, and spatial patterns of lacZ expression in transgenic larval tissues carrying D-raf and lacZ fusion genes. Further, we demonstrated that the D-raf gene is another target of the Zerknüllt (Zen) protein with observation of D-raf repression by Zen protein in cultured cells and its ectopic expression in the dorsal region of the homozygous zen mutant embryo. The evidence of DRE/DREF involvement in regulation of the D-raf gene obtained in this study strongly supports the idea that the DRE/DREF system is responsible for the coordinated regulation of cell proliferation-related genes in Drosophila.